PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA PADA SISWA KELAS 1 SDN 1 KEDIRI TAHUN PELAJARAN 2017/2018 - Muhammad Fauzy; Khairun Nisa; Siti Istiningsih (Indonesian Publication Center, 2020)
Students' motivation in mathematics learning about addition and subtraction low. For that the research was conducted. The purpose of this paper is to increase the motivation to learn math on addition and subtraction with media images on first grade second researchers based on theories and concepts associated with increased motivation to learn math on addition and subtraction with media images. The studies of this class action through four stages: planning, implementation, observation and reflection conducted in two cycles. Subjects in this study were 25 students of class I Elementary School Kediri. The technique of collecting data through observation, inquiry and documentation Motivation Scale. Technical analysis of the data using descriptive analysis. The analysis showed that the students' motivation increases. In the initial conditions before using media images student motivation achievement of 27.97%. After using media images in the first cycle increased student motivation achievement is 50.63%. Because it has not achieved the expected researchers then followed the second cycle. In the second cycle students' achievement motivation increased to 80.85%. The achievement of students' achievement motivation from the first cycle to the second cycle increased by 30.22%. Based on the results of this study concluded that the media images can increase the motivation to learn mathematics of the addition and subtraction of first grade students at SDN 1 kediri Year 2017/2018.